Novel phenyl‐POSS/polyurethane aqueous dispersions and their hybrid coatings. Issue 3 (3rd May 2013) - Hu, Jiankun; Li, Lian; Zhang, Siwei; Gong, Linbo; Gong, Shuling
ABSTRACT A facile and rapid preparation of 3‐(2‐aminoethylamino)propylheptaphenylPOSS (AA‐POSS), a special phenyl‐POSS that contains two functional amino groups (Scheme 1), is demonstrated by the corner‐capping method. Then AA‐POSS forms a series of novel phenyl‐POSS/PU aqueous dispersions. The structure of AA‐POSS has been confirmed by 1H, 13C, 29Si NMR, and ESI‐MS. The POSS/PU hybrid films are studied by Fourier transform infrared spectrometer (FT‐IR), gel permeation chromatography (GPC), scanning electron microscope (SEM), X‐ray diffraction (XRD) spectra, differential scanning calorimetry (DSC) analysis, and thermal gravimetric analyzer (TGA). FT‐IR and GPC are conducted to validate the chemical structure of the hybrid PU. The properties of hybrid films display significant changes with notable increases in Tg, thermal properties, tensile strength, as well as surface hydrophobicity. These changes are attributed to the incorporation of novel POSS into PU. Moreover, these significant material property enhancements are achieved at low levels of POSS incorporation (only 4%). © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1611–1620, 2013